Induction-assisted laser welding taking into account phase changes. Issue 4 (1st July 2019) - Kotlan, Václav; Hamar, Roman; Smolyanov, Ivan Alexandrovich; Doležel, Ivo
Abstract : Purpose: The paper aims to describe the modeling of the induction-assisted laser welding process taking into account the keyhole effect and phase changes in the material. Design/methodology/approach: A sophisticated mathematical model of the above heat treatment process is presented, taking into account the above phenomena and all available nonlinearities of the material. Its numerical solution is carried out using the finite element method incorporating algorithms for the deformation of geometry and solution of the flow field. Findings: Unlike various simplified models solved in the past, this approach incorporating a sophisticated model of heat transfer and flow of melt is able to reach a very accurate solution, differing only by a small error (not more than 8 per cent) from the experiment. Research limitations/implications: The presented model does not consider several subtle phenomena related to the evaporation of metal after irradiation of the material by a laser beam. In fact, at the heated spot, all three phases of the material coexist. The evaporated metal forms a capillary leak off and forms a cloud above the spot of irradiation. Due to the absorption of laser power in this cloud, the process of heating decelerates, which leads to a decrease in the process efficiency. Practical implications: The presented model and methodology of its solution may represent a basis for design of the process of laser welding. Originality/value: The main value is the proposal of numerical model for solution a complex multiphysical model with respecting several physical phenomena whose results are available in a short time and still with a good agreement with the experimental verification.